2000
DOI: 10.1081/clt-100100908
|View full text |Cite
|
Sign up to set email alerts
|

The Hemodynamic Effects of Cocaine During Acute Controlled Hemorrhage in Conscious Rats

Abstract: Although transient, cocaine blunted the hypotensive response to acute controlled hemorrhage and resulted in tachycardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Baseline HR was not measured in this protocol because the unanesthetized rat would not tolerate this external monitor. In a previous study, the HR in awake, unanesthetized male Sprague-Dawley rats was between 446 and 491 beats/min, 30 and another study reported an HR between 320 and 480 beats/min. 15 In this study, there appeared to be a slight slowing of the HR following administration of GBL compared with previous measurement.…”
Section: Limitationsmentioning
confidence: 93%
“…Baseline HR was not measured in this protocol because the unanesthetized rat would not tolerate this external monitor. In a previous study, the HR in awake, unanesthetized male Sprague-Dawley rats was between 446 and 491 beats/min, 30 and another study reported an HR between 320 and 480 beats/min. 15 In this study, there appeared to be a slight slowing of the HR following administration of GBL compared with previous measurement.…”
Section: Limitationsmentioning
confidence: 93%